A educação escolar na era da cultura das mídias: o corpomídia como paradigma desestabilizador de dispositivos de poder - Pinto, Rosana Nogueira (2013)
The object of this dissertation is to analyze some aspects of elementary education in Brazil, through some communication theories that explain conservative control devices which act incisively in school life. In the last ten years, there is a proliferation of bibliographies which suggest that we are immersed in media culture (at the expense of mass culture) and in new conceptions of work and of body (with emphasis on immaterial labor and non-docile bodies). However, in the case of elementary education, all of these transformations are gradual, and some cognitive patterns generated by mass communication persist. In the case of this dissertation, the corpusof analysis refers to some specific experiences in public education, of which the researcher has actively participated. In methodological terms, the discussions starts with the collaborationof Jesús Martín-Barbero (2003, 2009), who proposes rethinking education through communication, in line with the pedagogical proposals of Paulo Freire (1980, 2005, 2011) and other theories of communication which value the role of the body and recognize a mediaticbios (SODRÉ, 2009; GREINER; KATZ, 2005, 2010). Besides that, some fragments of the extensive work of Michel Foucault (1979, 2010) show themselves as essential in bringing to the discussion some important themes, among them the notion of micro-powers and docile bodies. Such studies help diagnose the devastating consequences of social education, which originate from the notion of the body as a vehicle or instrument. The expected result is the formulation of a preliminary critical reflection stating the relationship between some power devices of media culture and the ways in which education, and more specifically the education of the body, remains oppressive, despite all debates regarding media networks that favor the power and uniqueness of human beings